Implementasi Kurikulum 2013 Dalam Meningkatkan Mutu Pembelajaran Al Qur’an Hadits - Nashihin, Muhammad (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
The author tries to link the implementation of the 2013 Curriculum at Madrasah Aliyah Tarbiyatul Wathon to the improvement in the quality of learning the Al Qur'an Hadith, because there are significant differences between the 2013 Curriculum and the Education Unit Level Curriculum, starting from planning, implementation to evaluation in all formats much different and can be said to be a complement or complement to the previous curriculum format, namely the Education Unit Level Curriculum. This research was conducted regarding studies related to the Implementation of the 2013 Curriculum in Improving the Quality of Al-Qur'an Hadith Learning at Madrasah Aliyah Tarbiyatul Wathon Campurejo Panceng Gresik. In the implementation of learning the Al Qur'an Hadith Subject Teachers have implemented the contents of the Learning Implementation Plan based on the 2013 curriculum concept by using a Scientific Approach including observing, asking, trying, associating, communicating which are the characteristics of the curriculum, up to learning evaluation Al Qur'an Hadith Subject Teachers have applied the concept of authentic assessment in the 2013 Curriculum in the realm of attitudes, knowledge, and skills by using process, product, and attitude assessment models.